The Role of Knowledge and Attitude of Regular Students to Acceptance toward Special Educational Needs - Sheila Putri Fajrianti; Margaretha Purwanti (Journal of Educational, Health and Community Psychology, 2021)
These days, regular students’ behaviors still reflect a low acceptance of students with special educational needs (SEN). Previous studies have revealed that the crucial factors to examine are regular students’ knowledge about disabilities and attitudes. This study aims to determine the extent to which these two factors contribute to their acceptance of SEN. This quantitative research was conducted on 1248 participants from 14 public junior high schools in DKI Jakarta. Multiple linear regression analysis was run to determine peer acceptance from knowledge about disabilities and attitude. These variables statistically significantly contributed to peer acceptance, F(2, 1245) = 612.951, p < .05, R2 = .496. Both variables added statistically significantly to peer acceptance, p < .05. While both knowledge and attitude matter in peer acceptance towards SEN, implications for practice should also involve developing an intervention program that not only focuses on knowledge only but also targeting positive changes in attitudes. Keywords: peer acceptance, special educational needs students, adolescent, public schools